Підсудність кримінальних справ у Львові у XVI-XVIII ст. - Білостоцький, С.; Bilostotski, S. (Східноєвропейський національний університет імені Лесі Українки, 2016)
Стаття присвячена дослідженню юрисдикції судів Львова у кримінальних справах в XVI-XVIII ст. Проаналізовано правові акти, що визначають систему і компетенцію судів. Доведено, що судова система Львова в XVI - XVIII ст. була досить складною і заплутаною. Жителі Львова в залежності від правового статусу і місця проживання підпадали під юрисдикцію різного права - магдебурского, земського, національних громад. Справи були підсудні міському магдебурзьким суду, гродським, змішаним, складеним, королівським судам і судам вірменської та єврейської націй. Відсутність принципів визначення підвідомчості і підсудності кримінальних справ викликали значні зловживання щодо їх розслідування, судового розгляду та виконання вироку. The article is devoted to the study of jurisdiction of Lviv courts in criminal cases in the XVI - XVIII centuries. It analyzes legal acts that determine the system and the competence of the courts. It is proved that the judicial system in Lviv in XVI - XVIII centuries was quite complicated and confusing. Residents of Lviv, depending on the legal status and place of residence, fell under the jurisdiction of different laws – Magdeburg, Zemsky, laws of national communities and accordingly the criminal cases were the jurisdiction of the city Magdeburg trial, urban, mixed, municipal, royal courts and the courts of the Armenian and Jewish nations. Municipal courts had the jurisdiction over cases of burghers. Court of bailiff examined cases of light offenses. Armenians fell under the jurisdiction of the mixed courts. Jews were excluded from the jurisdiction of municipal courts and fell under jurisdiction of the provincial, composed, royal courts and the Court of Rabin. The absence of principles for determining jurisdiction of criminal cases caused considerable abuses against their investigation, the trial and execution of the sentence.
Jurisdiction of Criminal Cases in Courts of Lviv in XVI-XVIII Centuries
Keywords: війт; війтівсько-лавничий суд; складені суди; підсудність; магдебурзьке право; євреї; вірмени; viyt; Magdeburg city court; mixed and composed courts; Jurisdiction; Magdeburg Law; Jews; Armenians